Two Immigrants with Tuberculosis of the Ear, Nose, and Throat Region with Skull Base and Cranial Nerve Involvement - Renate A. Richardus; Jeroen C. Jansen; Stefan C. A. Steens; Sandra M. Arend (Case Reports in Medicine)
We report two immigrants with tuberculosis of the skull base and a review of the literature. A Somalian man presented with bilateral otitis media, hearing loss, and facial and abducens palsy. Imaging showed involvement of both mastoid and petrous bones, extending via the skull base to the nasopharynx, suggesting tuberculosis which was confirmed by characteristic histology and positive auramine staining, while Ziehl-Neelsen staining and PCR were negative. A Sudanese man presented with torticollis and deviation of the uvula due to paresis of N. IX and XI. Imaging showed a retropharyngeal abscess and lysis of the clivus. Histology, acid-fast staining, and PCR were negative. Both patients had a positive Quantiferon TB Gold in-tube result and improved rapidly after empiric treatment for tuberculosis. Cultures eventually yielded M. tuberculosis. These unusual cases exemplify the many faces of tuberculosis and the importance to include tuberculosis in the differential diagnosis of unexplained problems.